A new species of Glipa LeConte, 1859 subgenus Stenoglipa Franciscolo, 1952 (Coleoptera: Mordellidae: Mordellini) from the Philippines - Ruzzier, Enrico (Zootaxa, 2018)
The mordellid fauna of the Philippines is still poorly known and only a few scattered contributions on this area exist (Ray 1930a,b; Shiyake 1997; Franciscolo 2000; Horák 2007; Kiyoyama 2010; Takakuwa 2000, 2011).